Export opportunities and obstacles of Bangladesh’s RMG sector : a case study on Aman Textile Ltd. - Tama, Sumaiya Kabir (BARC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.